2019
DOI: 10.1002/pbc.27832
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Columbus II: A novel c.1075G>T mutation in the FGG gene causing hypodysfibrinogenemia and thrombosis in an adolescent male

Abstract: Hypodysfibrinogenemia, the least frequently reported congenital fibrinogen disorder is characterized by low circulating levels of a dysfunctional protein, and is associated with phenotypic features of both hypo‐ and dysfibrinogenemia. Herein, we report an adolescent male with unprovoked venous thromboembolism and hypodysfibrinogenemia. Patient had recurrent, progressive thrombosis despite therapeutic anticoagulation with both low molecular weight heparin and warfarin. He had clinical and radiological improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Fibrinolysis occurs when t-PA binds to γp.338-350 (312-324, mature protein nomenclature) region [32] on the fibrin surface. In this region, two thrombotic variants, γp.S358C [34] and G359C [35], have been reported. In the latter case, the proximity of the γp.G359C mutation to the Cys 352 -Cys 365 disulfide bond may disrupt this disulfide bond [35], resulting in thrombotic manifestation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fibrinolysis occurs when t-PA binds to γp.338-350 (312-324, mature protein nomenclature) region [32] on the fibrin surface. In this region, two thrombotic variants, γp.S358C [34] and G359C [35], have been reported. In the latter case, the proximity of the γp.G359C mutation to the Cys 352 -Cys 365 disulfide bond may disrupt this disulfide bond [35], resulting in thrombotic manifestation.…”
Section: Discussionmentioning
confidence: 98%
“…In this region, two thrombotic variants, γp.S358C [34] and G359C [35], have been reported. In the latter case, the proximity of the γp.G359C mutation to the Cys 352 -Cys 365 disulfide bond may disrupt this disulfide bond [35], resulting in thrombotic manifestation. These reports suggested that amino acid substitutions from or to Cys around γp.352 are prone to arouse thrombotic complications.…”
Section: Discussionmentioning
confidence: 98%